Hubungan Endometriosis dengan Infertilitas pada Pasien Poliklinik Obstetri Ginekologi dan Klinik Fertilitas Sekar RSUD Dr. Moewardi Surakarta - Shabrina, Irsalina Nur; Oepomo, Tedja Danudjo; ., Yulia Sari (Nexus Kedokteran Klinik, 2014)
Background: Women with endometriosis have a difficult pregnancy. Nowadays, infertility becoming a difficult problem towards married persons, especially for the wife,Â  from this research would known the fact is it true that endometriosis is a disease that is often found in infertil woman. This study aims is to determine the relationship between endometriosis and infertility among the patients at RSUD Dr. Moewardi Surakarta. Methods: This study was an observational analytic studies, with case-control approach. Data were taken from female patients who had been hospitalized on the Obstetrics Gynecology Clinic and Sekar Fertility Clinic of RSUD Dr. Moewardi from January 2012 to July 2013, interviews were conducted with a questionnaire to find out the history of parity. Data were analyzed by chi-square statistical test (Î± = 0.05). Results: Based on the research towards 44 sampels, consisted of 22 samples of cases andÂ  22 samples of controls were identified that there were 16 infertile women with endometriosis, 2 fertile women who have endometriosis, 6 infertile women without endometriosis, and 20 fertile women without endometriosis. Chi Square statistical test results showed a significant relationship between endometriosis with infertility with p = 0.00 (p <0.05). Conclusions: There is a statistically significant relationship between endometriosis with infertility (p = 0.00) among the patients of RSUD Dr. Moewardi Surakarta. Keywords: endometriosis, infertility Â